The Dictum de Omni et Nullo: Toward a Transformative Shift in Educational Paradigms Beyond UN-Led Contradictory Global Frameworks - Sravan, Gowthami Kumar (Journal of Educational Research and Policies, 2026)
Aristotle’s dictum de omni et nullo presupposes that the major premise [constitution-in-itself] must be universal and the minor premise [thing-in-itself] must be affirmative. This article potentially argues that the well-established UN-led global paradigm is flawed in the context of the dictum. UNO-led global paradigm is both contrary to the universal major premises of the dictum such as Newton’s third Law-‘equal & opposite’ [self-contradictory in the context of philosophy] and contradictory to the affirmative minor premises of the dictum such as Einstein’s binary pulsar [paradoxical in the context of science]. So, the paper calls for the need of a transformative-shift in institutional education system towards nature-driven reciprocal paradigm, which is based on the principles of ‘equal and opposite’ [creation in pairs] and ‘odd and event contrast’ [three-dimensional elliptical orbit viewed from two-dimensional perspective]. The paper rationally advocates for such a nature-driven reciprocal paradigm that incorporates the existential imports of sanctity of education, significance of scientific certainty, inherent dignity, moral solidarity, freedom of conscience, liberty of faith-belief- thought-expression-worship, dialectic of truth-right-justice, fundamental duties & moral responsibilities, holistic development of our axiological aspects and one dimensional time towards right direction, greatest happiness of the greatest number of people [utilitarian liberation], and common end [public interest].